2020
DOI: 10.30813/bricolage.v6i01.2065
|View full text |Cite
|
Sign up to set email alerts
|

Gender Performance Discourse on Tinder Profile Pictures in London, Uk – A Social Semiotics Study

Abstract: Cyclical and bidirectional relationship(s) between technology and today’s romantic gratifications have reformed how people seek romance. On another end, gender performances largely underpin humans’ romantic gratification. This is where Tinder, as a dating application, affords unique opportunities for those seeking romances through portraying gender performances. A number of studies concluded that, in romance-seeking ventures, male’s masculinity and female’s femininity generally remained conformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Online news formatting is no stranger to a variety of font sizes and colors in a Mondrian or color-block tradition. The use of color blocking, literature points, may suggest an element of seriousness and class thereby heightening an element of trustworthiness as well as suggesting an element of accountability to the text (Rorong et al, 2020;Rovino et al, 2020). On top of that, the use of metaphors in all three news was also found, which suggests subtlety in meaning transmission.…”
Section: Microstructure (Rhetorical: Metaphor Expression and Graphic)mentioning
confidence: 99%
“…Online news formatting is no stranger to a variety of font sizes and colors in a Mondrian or color-block tradition. The use of color blocking, literature points, may suggest an element of seriousness and class thereby heightening an element of trustworthiness as well as suggesting an element of accountability to the text (Rorong et al, 2020;Rovino et al, 2020). On top of that, the use of metaphors in all three news was also found, which suggests subtlety in meaning transmission.…”
Section: Microstructure (Rhetorical: Metaphor Expression and Graphic)mentioning
confidence: 99%
“…Gender bias, in fact, prevail in the several aspects of daily basis. Rovino and Rorong (2019) examined tinder application as semiotic analysis on its gender performance. The result revealed that although generally tinder user remained to conform to the traditional gender ideology that is masculine-centric and feminine-centric, the subversive gender performances that went against the traditionalist view on gender were also noticeably.…”
Section: Gender Biasmentioning
confidence: 99%